Spinning the wheel of design: evaluating geoportal Graphical User Interface adaptations in terms of human-centred design - Gkonos, Charalampos; Iosifescu Enescu, Ionut; Hurni, Lorenz (International journal of cartography, 2019)
Geoportals are used to support the sharing of geospatial data for various purposes. In recent years, the importance of such geoportals in an academic environment is highly recognized. Equipped with the latest and most detailed spatial datasets these academic geoportals can support universities in numerous activities including research and teaching. One of the key characteristics that significantly influences the effectiveness of the academic geoportals is their Graphical User Interface (GUI). GUI designers can now benefit from emerging web technologies that assist in the production of intuitive interfaces to ensure high efficiency, good User Experience (UE), maximum usability and simultaneously the minimum cognitive workload. In this paper, we introduce the new GUI of the Geodata Versatile Information Transfer environment geoportal, and we present the results of a between-subjects study with 20 participants for the evaluation and comparison of the previous and the latest version. The results show that the GUI adaptations done, have a positive influence to several indicators like efficiency, UE, usability and cognitive workload. Our findings additionally reveal the weaknesses of the latest design and give constructive feedback in order to identify in which areas we should further improve the GUI to keep spinning the wheel of design.